Expressão diferencial de proteínas durante a maturação sexual de Angiostrongylus cantonensis em infecção experimental de Rattus norvegicus - Oliveira, Camila Krug de (2012)
The two parasites in the genus Angionstrongylus that cause disease in humans are Angiostrongylus costarisensis and Angiostrongylus cantonensis. They have different target organs: A. costarisensis is located in the mesentery and causes eosinophilic ileocolitis, whereas A. cantonensis is a neurotropic parasite responsible for eosinophilic meningoencephalitis. Based on several indications that the sexual maturation is associated with increased pathogenesis in angiostrongylid worms, proteomic analysis was performed on A. cantonensis protein samples, to describe differential protein expression between 21 and 42 days post infection. Triplicated bidimensional electrophoresis was submitted to analysis and 11 proteins were found to be exclusively expressed after sexual maturation. Acetate kinase was the only protein that could be identified after mass spectrometry (LC-MS/MS). Since acetate is an important end-product of the energy metabolism among many parasites but not among their mammalian hosts, acetate formation is an attractive target for the development of new anti-parasitic drugs. Furthermore, studying the adaptations in parasite metabolisms can result in an increased understanding of the host-parasite interaction. This data open opportunities for control interventions and new strategies for molecular diagnosis.